2021
DOI: 10.1126/science.aax3972
|View full text |Cite
|
Sign up to set email alerts
|

60Fe and244Pu deposited on Earth constrain the r-process yields of recent nearby supernovae

Abstract: Half of the chemical elements heavier than iron are produced by the rapid neutron capture process (r-process). The sites and yields of this process are disputed, with candidates including some types of supernovae (SNe) and mergers of neutron stars. We search for two isotopic signatures in a sample of Pacific Ocean crust—iron-60 (60Fe) (half-life, 2.6 million years), which is predominantly produced in massive stars and ejected in supernova explosions, and plutonium-244 (244Pu) (half-life, 80.6 million years), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
118
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(154 citation statements)
references
References 101 publications
18
118
1
Order By: Relevance
“…The left panel of Fig. 6 compares the AION and AEDGE sensitivity curves with the GW spectrum predicted by the Ac3G model for the neutrino gravitational memory signal from a SN collapse at a distance of 100 pc (similar to the distances of nearby Tucana-Horologium [50] and Scorpio-Centaurus [51] stellar associations that may have hosted SN explosions within the past few million years [52]), 1 kpc and 10 kpc (a range including the galactic centre). We see that a SN at 100 pc should be detectable by AION-km, whereas a SN at 1 kpc would be at the limit of AION detectability.…”
Section: (B) Supernovaementioning
confidence: 99%
“…The left panel of Fig. 6 compares the AION and AEDGE sensitivity curves with the GW spectrum predicted by the Ac3G model for the neutrino gravitational memory signal from a SN collapse at a distance of 100 pc (similar to the distances of nearby Tucana-Horologium [50] and Scorpio-Centaurus [51] stellar associations that may have hosted SN explosions within the past few million years [52]), 1 kpc and 10 kpc (a range including the galactic centre). We see that a SN at 100 pc should be detectable by AION-km, whereas a SN at 1 kpc would be at the limit of AION detectability.…”
Section: (B) Supernovaementioning
confidence: 99%
“…A detection of 244 Pu on Earth thus would represent a record of r-process nucleosynthesis near the solar system, similar to what has been found with 60 Fe from core-collapse supernovae. The ocean crust samples therefore have also been searched for rare nuclei at higher masses, which could shed light on r-process origins (Wallner et al 2015(Wallner et al , 2021. Detecting several nuclei of 244 Pu in an analysis of a consistent set of ocean crust samples showing also 60 Fe led Wallner et al (2021) to conclude that core-collapse supernovae of the frequently-occurring type cannot be responsible for r-process materials traced by 244 Pu, as a much higher detection count would be expected.…”
Section: Interstellar Environments Of Nucleosynthesis Sourcesmentioning
confidence: 99%
“…The ocean crust samples therefore have also been searched for rare nuclei at higher masses, which could shed light on r-process origins (Wallner et al 2015(Wallner et al , 2021. Detecting several nuclei of 244 Pu in an analysis of a consistent set of ocean crust samples showing also 60 Fe led Wallner et al (2021) to conclude that core-collapse supernovae of the frequently-occurring type cannot be responsible for r-process materials traced by 244 Pu, as a much higher detection count would be expected. Of course, propagation of ejecta from a nucleosynthesis event into ocean floor sediments is a complex sequence of different astro-physical processes.…”
Section: Interstellar Environments Of Nucleosynthesis Sourcesmentioning
confidence: 99%
“…In particular, the origin of r-process in the early Galaxy as observed in very metal-poor stars (see e.g., a recent review by Cowan et al (2021) and the references therein) as well the evolution r-process elements in the disk at late times may require additional sources (Côté et al 2019a). A num-E-mail: projjwal.banerjee@gmail.com ber of sites have been proposed as candidates for additional r-process sources that include NS -black hole (BH) mergers (Lattimer & Schramm 1974;Rosswog 2005;Kyutoku et al 2013;Foucart et al 2014), neutrino-driven winds from corecollapse supernovae (CCSNe) (Woosley et al 1994;Takahashi et al 1994;Qian & Woosley 1996;Arcones & Thielemann 2013), magneto-rotational supernovae (MRSNe) (Nishimura et al 2006;Winteler et al 2012;Mösta et al 2018), collapsars (Siegel et al 2019;Miller et al 2020), accretion disk outflows during the common envelope phase of NS-massive star system (Grichener & Soker 2019), CCSNe triggered by the hadron-quark phase transitions (Fischer et al 2020), etc. In this regard, measurement of the abundances of shortlived radioactive isotopes (SLRIs) that are exclusively produced by r-process in the early solar system (ESS), as determined from meteorites as well as Earth's deep-sea sediments, can be used to infer the properties of r-process events that occurred in the Solar neighbourhood (Wallner et al 2015;Hotokezaka et al 2015a; Bartos & Marka 2019;Côté et al 2021;Wallner et al 2021). In a recent study Côté et al (2021) showed that the observed ratio of the abundances of r-process SLRIs 129 I and 247 Cm present in the ESS can be used to constrain the "last" r-process event that contributed to the solar abundance before the formation of the SS.…”
Section: Introductionmentioning
confidence: 99%